DETERMINANTS OF WORK MOTIVATION AMONG DOCTORS AT COMMUNITY HEALTH CENTERS IN INDONESIA - Rusdiana, Rusdiana; Faisya, Achmad Fickry; Idris, Haerawati (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Introduction: Effective work motivation among healthcare professionals significantly enhances health service performance and plays a pivotal role in improving service quality. Aims: This study aims to analyze the determinants influencing work motivation among doctors at community health centers in Indonesia. Methods: This study employed a quantitative approach with a cross-sectional design, utilizing secondary data from the 2017 Indonesian Workforce Research in the Health Sector. The study sample comprised 9,988 respondents. Logistic regression was employed for data analysis. Results: In 2017, 55.1% of doctors at community health centers in Indonesia reported high work motivation. Significant correlations were identified between work motivation and various factors: individual characteristics (age, education, marital status, position), intrinsic factors (training and continuing education), extrinsic factors (salary/wages, work area), financial incentives (performance allowances, capitation fund incentives), and non-financial incentives (official vehicles) (p < 0.05). Among these, the type of position was identified as the most dominant factor influencing work motivation (p < 0.05; prevalence ratio (PR) = 1.805 CI 95% [1.608-2.028]). Conclusion: Work motivation among doctors at community health centers in Indonesia is significantly influenced by individual characteristics, intrinsic and extrinsic factors, as well as financial and non-financial incentives, with the type of position being the most dominant factor. To enhance motivation and improve healthcare services, policymakers should strengthen career development, expand training opportunities, improve financial and non-financial incentives, and implement targeted retention strategies, especially in underserved areas. Keywords: Community health center, doctor, Indonesia, work motivation